Enhancers in polymeric nonviral gene delivery systems. Issue 1 (27th August 2020) - Yang, Zhiyu; Guo, Zhaopei; Tian, Huayu; Chen, Xuesi
Abstract: Gene therapy is a promising therapeutic tool for cancers and inherited diseases. For successful gene therapy, gene delivery systems must be designed reasonably to allow DNA or other nuclear acids to be taken up by the cancer cells and then transported to target location for function. In the research of gene delivery systems, polymeric nonviral carriers for genes have attracted much attention. However, polymeric gene delivery systems suffer from low transfection efficiency. Various strategies have been developed for improving efficacy of polymeric gene delivery systems. These strategies can be categorized into covalent strategies and noncovalent strategies according to the way how the functional unit is combined with the carrier. Noncovalent strategies in improving gene transfection efficiency are simply mixing additional functional components with carriers. These relatively independent functional materials are named gene delivery enhancers here. In this review, we focus on enhancers in polymeric gene delivery systems. We discuss structures and enhancement mechanisms of enhancers in the order of the stages in which they function in gene delivery process. Barriers of in vitro gene delivery are also reviewed briefly. Abstract : High‐efficiency gene delivery systems are of great significance for successful gene therapy. In this review, the authors summarize noncovalent strategies enhancing in vitro gene transfection efficiency by simply adding enhancers to gene delivery systems.